Characterization of late diagnosis of oral cancer in a Brazilian city - Manuela Gouvêa Manuela; Danúbia Roberta de Medeiros Nóbrega; Gabriella de Vasconcelos Neves; Hianne Cristinne de Morais Medeiros; Jozinete Vieira Pereira; Daliana Queiroga de Castro Gomes (Editorial Ciencias Médicas, 2015)
Introduction: oral cancer in Brazil still presents high incidence and mortality rates and has different characteristics throughout the national territory. Although in most cases the diagnosis is late, there is a great possibility for cure when patients are treated early. Objective: to describe the sociodemographic profile of patients with oral squamous cell carcinoma and the possible etiological factors associated. Methods: this was a descriptive prospective cross-sectional study carried out in Napoleão Laureano Hospital, state of Paraíba, from January 2012 to May 2013. The study included patients with advanced-stage oral squamous cell carcinoma identified during clinical examination and confirmed by histopathology. The following variables were assessed: age, sex, comorbidity, smoking, alcohol use, tumor location, time of development, clinical staging, histopathological grading and proposed treatment. Results: a total of 15 cases of patients with stage III and IV oral squamous cell carcinoma were found. Of these, 80 % were males with a mean age of 62.59 years and lesions affecting predominantly the mouth floor, followed by the tongue. The most common sign was the presence of tumor greater than 3.0-cm diameter, including ulcerated, leukoplastic and erythroplastic areas, in addition to pain and difficulty in feeding and phonation. Conclusion: the majority of patients identified, with advanced-stage squamous cell carcinoma showed moderate cellular differentiation between stages III and IV, and was composed by males with smoking and alcohol drinking habits in the seventh decade of life.